Four oral iron supplements for treating iron-deficiency anemia during pregnancy in China: a cost-effectiveness and budget analysis - Zhang, Ling; Zeng, Zixing; Zhang, Biyang; Gu, Hai (Frontiers in Public Health, 2025)
ObjectivesThis study has two primary objectives: (a) to conduct a comparative cost-effectiveness analysis of four commonly used oral iron supplements for treating iron-deficiency anemia during pregnancy in China, including ferrous succinate sustained-release tablets, polysaccharide-iron complex capsules, iron protein succinylate oral solution, and iron dextran oral solution; and (b) to assess the budget impact of including ferrous succinate sustained-release tablets in the National Reimbursement Drug List (NRDL) on national medical insurance expenditures.MethodsA decision tree model was developed to analyze the cost-effectiveness based on treatment efficacy derived from a network meta-analysis. A sensitivity analysis was conducted to address uncertainties in the parameters. Subsequently, a budget impact analysis model was utilized to calculate the effect of including ferrous succinate sustained-release tablets in the NRDL on the expenditures of employee medical insurance funds, resident medical insurance funds, and the total medical insurance fund expenditures.ResultsThe cost-effectiveness analysis showed that ferrous succinate sustained-release tablets are a cost-effective treatment option. When compared to polysaccharide-iron complex capsules, the additional cost per effect of the ferrous succinate sustained-release tablets is 3.23. If these tablets are included in the NRDL, the total medical insurance expenditure on oral iron preparations for treating iron-deficiency anemia in pregnant women is expected to decrease from 160.14 million to 156.82 million between 2025 and 2027.ConclusionFerrous succinate sustained-release tablets are a cost-effective treatment option for iron-deficiency anemia during pregnancy in China.